UNCLOS 30 Years’ Implementation: The role of the Constitution for the Oceans in Responding to Climate Change and Vietnam's Actions - Long, Nguyen Thanh; Cuc, Nguyen Thi Kim (VNU Journal of Science: Legal Studies; Vol 42 No 1DO - 10.25073/2588-1167/vnuls.4761, 2026)
Considered the Constitution for the Oceans, the 1982 United Nations Convention on the Law of the Sea (UNCLOS 1982) is a multilateral international treaty that covers the most important legal issues related to seas and oceans. Since its entry into force on 16 November 1994, UNCLOS 1982 has demonstrated its importance in many aspects, contributing to peace and stability at sea. Meanwhile, climate change is a global environmental challenge that directly affects human health and life. Addressing climate change is a shared responsibility of the international community, requiring states, including Vietnam, to be proactive in enacting and effectively implementing relevant legal regulations. In this context, this article aims to study and evaluate the role of UNCLOS 1982 in the global fight against climate change. Using analytical and comparative methods, the article first provides an overview of UNCLOS 1982 and climate change, and explores their interrelationships. It then analyses specific provisions of UNCLOS 1982 on climate change to assess Vietnam's capacity to respond to climate change. Finally, the article reviews and discusses the current provisions of Vietnamese law on climate change and analyses their relationship with UNCLOS 1982.  In particular, the article evaluates the role of the International Tribunal for the Law of the Sea (ITLOS) in addressing climate change by examining its Advisory Opinion dated May 21, 2024. Based on the analysis, the article proposes some recommendations to enhance Vietnam’s proactive engagement in the global response to climate change.